A comparative study on heavy metals concentration between house with and without home water filter / Noor Suhadah Abdul Aziz - Abdul Aziz, Noor Suhadah (2010)
Lack access to clean and safe drinking water is a public health hazard. Due to the poor quality of supplied drinking water, respondents start to take additional measure by purchasing and installing their own home drinking water filter to improve the quality of their drinking water. A comparative study was conducted to determine heavy metals level (Lead, Cadmium, Copper and Iron) in respondent's tap water, to compare heavy metals level between filtered and unfiltered water and to compare the probable hazard associated with exposure to heavy metals in drinking water between respondents consuming filtered water and unfiltered water (n=140). Total of 60 tap water samples were collected and were analyzed using Graphite Furnace Atomic Absorption Spectrometry (GFAAS). Results shows that level of Lead (0.02 mg/L) and Iron (0.63 mg/L) in respondent's tap water was violated the maximum acceptable value for Lead (0.01 mg/L) and Iron (0.3 mg/L) under National Standard For Drinking Water Quality 2004. There were significant differences in heavy metals level exist between filtered and unfiltered water (P < 0.05). Heavy metals level in unfiltered water was high compared to filtered water. Data also showed that there were significant differences in health hazard exist between respondents consuming filtered water and unfiltered drinking water (P < 0.05). Respondents consuming unfiltered water shown to get adverse health effect associated with the exposure to heavy metals in their drinking water. It was revealed that the use of home water filter can remove certain amounts of heavy metals in drinking water thus reduce health hazard associated to that particular contaminants.